The Use of Agricultural Waste Straw to Enhance Loess Shearing Behaviour: An Experimental Investigation - Lin Wang; Wen-Chieh Cheng; Zhong-Fei Xue (Advances in Materials Science and Engineering)
Strata erosion in northwest China has become an engineering concern as a result of overdevelopment of land. This issue is more distinct for loess soil than other soils since it is characterised by metastable microstructure, high porosity, and water sensitivity. This study explores the potential for the use of agricultural waste straw as a recycled reinforcement material to form the enhanced shearing behaviour towards preventing instability of the loess body. The stress-strain relation and the pore pressure behaviour of Lantian loess and reinforced Lantian loess were studied using the conventional triaxial compression (CTC) stress path for three different confining pressures. Comparison with Jingyang loess and Delhi silt of similar relative fraction of silt to clay, sheared under the reduced triaxial compression (RTC) stress path and the reduced triaxial extension (RTE) stress paths, respectively, was conducted, with emphasis on strength uniqueness and critical state behaviour, to shed light on the effect of waste straw inclusions. The results indicate that the stress path in undrained compression and extension tests had a pronounced effect on the stress-strain relation of the studied soils. Insertion of the waste straw in Lantian loess restrained the development of volumetric deformation, producing higher pore pressures than Lantian loess (unreinforced). This study explores an exciting potential for the use of agricultural waste straw to prevent instability of the loess body in hilly-gullied regions of northwest China when subjected to quick surface thick fills.